Supply Chain Management: Some Insights From Indian Manufacturing Companies - Jharkharia , Sanjay; Shankar, Ravi (Asian Academy of Management (AAM), 2004)
Some issues such as inventory management, IT-enablement of supply chains, and buyersupplier relationships are at the core of supply chain research. Some other issues such as postponement, top management commitment, and disparities in trading partners' capability influence these core issues. Some hypotheses have been proposed to assess such influences. Through a questionnaire-based survey for Indian manufacturing companies, these hypotheses have been tested. It is observed from this research that information sharing and top management commitment have important roles towards the effectiveness of a supply chain. The findings also establish relationships among many important issues of supply chain management. The paper ends with the discussion and implications of this research.